Calidad del servicio y satisfacción del cliente externo de la Caja Municipal de Ahorro y Crédito Piura agencia Iquitos mayo 2020 - Charpentier Merino, Linda Alexandra (2022)
The research work entitled Quality of Service and External Customer Satisfaction of de Municipal Savings and Credit Fund Piura Agency Iquitos, May, 2020 and, aims to determine the relationship between the quality of the service and level of satisfaction of the external customers of the Municipal Savings and Credit Fund Piura Iquitos Agency, May 2020, also set as specific objectives to determine which of the elements of the quality of the service has greater perception by the external client of the Municipal Savings and Credit Fund Piura Iquitos Agency, May 2020 and determine which of the elements of de quality of the service has least perceptions by the external client of de Municipal Savings and Credit Fund Piura Iquitos Agency, May, 2020. The research concludes that the relationship between the quality of the service and the level of satisfactions of the external clients of the Municipal Savings and Credit Fund Piura Agency Iquitos, May, 2020 is direct and strong with a Rho de Spearman correlation coefficient of 0.570 a p valius of 0.000 and a significance level of 0.01.